2007
DOI: 10.1585/pfr.2.s1079
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Molecular and Atomic Ions in Recombination Plasma

Abstract: Measurements of the densities of the molecular and atomic ions (n H + , n H2 + , n H3 + ) were carried out in hydrogen recombination plasma in the linear divertor plasma simulator, TPD-SheetIV. The molecular and atomic ion currents were detected using an omegatron mass analyzer. The ground-state vibrational temperature of hydrogen molecules T vib is obtained by measurement with VUV emission spectroscopy. Taking into account of T vib , a zero-dimensional model using the relevant rate balance equations was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…However, the role of molecular ions in the hydrogen plasma is still under discussion and various conclusions have been derived from the analysis of different experiments. [3][4][5][6] On the other hand, it has been pointed out that even the contribution of recombination is not critical for a reduction in ion flux. 7) Recently, it has been reported that in a typical high-density plasma, H 2 (v) molecules assist dissociation (MAD) and ionization (MAI) before they contribute to recombination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the role of molecular ions in the hydrogen plasma is still under discussion and various conclusions have been derived from the analysis of different experiments. [3][4][5][6] On the other hand, it has been pointed out that even the contribution of recombination is not critical for a reduction in ion flux. 7) Recently, it has been reported that in a typical high-density plasma, H 2 (v) molecules assist dissociation (MAD) and ionization (MAI) before they contribute to recombination.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we have carried out the experimental observation and modeling of molecular ions in hydrogen plasma in a linear plasma device, TPD-SheetIV. 5,6) Measurements of the densities of molecular and atomic ions were carried out in hydrogen plasma with a hydrogen gas puff. The molecular and atomic ion currents were detected using an ''omegatron'' mass analyzer, while the electron density and temperature were measured using a Langmuir probe and a double probe.…”
Section: Introductionmentioning
confidence: 99%
“…[9,14,15] uniform magnetic field up to 0.1 T in the experimental region. The hydrogen plasma was generated at a hydrogen gas flow of 75 sccm, with a discharge current of 30-100 A.…”
Section: Experimental Apparatus and Methodsmentioning
confidence: 99%
“…In high neutral density such as detached divertor plasma, it is necessary to take into account of radiation trapping to experimental investigation of the VUV spectroscopy [9,18]. In case of the consideration of radiation trapping, the brightness of line will be in the ratio of their spontaneous emission coefficients.…”
Section: Modeling the Vuv Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation